The Relationship of Self-Concept and Work Satisfaction with Teachers Performance of Islamic Elementary School of Tebing Tinggi City - Siti Zahara; Candra Wijaya (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
One of the basic things that affect the performance of teachers in carrying out their duties is self-concept. Self-concept is all ideas, thoughts, beliefs and convictions that individuals know about themselves and influence individuals in dealing with others. An important factor in self-concept is that self-concepts are learned through individual experiences and interactions with others. In addition, self-concept is a critical and basic aspect of the formation of individual behavior, developing rapidly and together with the development of speech. There is a positive and significant relationship between the self-concept of teachers in the State of Madrasah Ibtidaiyah Tebing Tinggi with the performance of teachers at the State Madrasah Ibtidaiyah in Tebing Tinggi. This means that the higher and positive self-concept, the higher and positive the performance of teachers in State Madrasah Ibtidaiyah Tebing Tinggi by providing an effective contribution of 28.7%. This means that the variation that occurred in the teacher's self-concept variable Tebing Tinggi State Madrasah Ibtidaiyah was 28.7% predictable in improving the performance of teachers at State Madrasah Ibtidaiyah in Tebing Tinggi. There is a positive and significant relationship between job satisfaction with the performance of teachers at State Madrasah Ibtidaiyah in Tebing Tinggi. This means that the higher and positive job satisfaction of teachers at State Madrasah Ibtidaiyah in Tebing Tinggi city, the higher and positive the performance of teachers in State Madrasah Ibtidaiyah Tebing Tinggi by making an effective contribution of 32%.